The impact of access to finance and environmental factors on entrepreneurial intention: The mediator role of entrepreneurial behavioural control - Thu Thuy Nguyen (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to test the direct and indirect impact of environmental and individual determinants on entrepreneurial intention with perceived entrepreneurial behavioural control as a mediating variable. Research Design & Methods: A cross-sectional quantitative research was conducted using structural equation modelling analysis with a sample consisting of 635 students in 11 universities in Vietnam. Findings: The results reveal that perceived environmental factors are significantly related to students' perceived entrepreneurial behavioural control so that entrepreneurial behavioural control becomes a mediator through which those environmental factors influence entrepreneurial intention. Access to finance is insufficient to influence entrepreneurial intention unless combined with entrepreneurial behavioural control. Implications & Recommendations: The research findings have implications for policy-makers in fostering graduates' entrepreneurship in emerging countries. Contribution & Value Added: The survey provides evidence supporting the theoretical arguments that exogenous factors affect perceived entrepreneurial behavioural control and impact entrepreneurial intention through the individual's perceptions of behavioural control.
Keywords: L26; M13; 330; access to finance; entrepreneurial intention; perceived environment barriers; perceived behavioural control; university environment; SEM